Diagnosis and therapeutic monitoring of inborn errors of metabolism in 100,077 newborns from Jining city in China - Chi-Ju Yang; Na Wei; Ming Li; Kun Xie; Jian-Qiu Li; Cheng-Gang Huang; Yong-Sheng Xiao; Wen-Hua Liu; Xi-Gui Chen (BMC, 2018)
Abstract Background Mandatory newborn screening for metabolic disorders has not been implemented in most parts of China. Newborn mortality and morbidity could be markedly reduced by early diagnosis and treatment of inborn errors of metabolism (IEM). Methods of screening for IEM by tandem mass spectrometry (MS/MS) have been developed, and their advantages include rapid testing, high sensitivity, high specificity, high throughput, and low sample volume (a single dried blood spot). Methods Dried blood spots of 100,077 newborns obtained from Jining city in 2014-2015 were screened by MS/MS. The screening results were further confirmed by clinical symptoms and biochemical analysis in combination with the detection of neonatal deficiency in organic acid, amino acid, or fatty acid metabolism and DNA analysis. Results The percentages of males and females among the 100,077 infants were 54.1% and 45.9%, respectively. Cut-off values were established by utilizing the percentile method. The screening results showed that 98,764 newborns were healthy, and 56 out of the 1313 newborns with suspected IEM were ultimately diagnosed with IEM. Among these 56 newborns, 19 (1:5267) had amino acid metabolism disorders, 26 (1:3849) had organic acid metabolism disorders, and 11 (1:9098) had fatty acid oxidation disorders. In addition, 54 patients with IEM were found to carry mutations, and the other 2 patients had argininemia. Conclusions Fifty-six cases of metabolic disorders in Jining were confirmed via newborn screening (NBS) by MS/MS. Early diagnosis and treatment are crucial for the survival and well-being of affected children. A nationwide NBS program using MS/MS is recommended, especially in poor areas of China.